(untitled) (Journal of Fiber Bioengineering and Informatics, 2015)
Texture is indispensable in image-based rendering. In order to obtain realistic and aesthetic texture, a simple and effective texture synthesis method based on vector field is presented in this paper. A sufficient large, progressively-variant, aperiodic texture can be generated from a small texture sample based on the proposed method. The main contributions in this method are anisometric synthesis and appearance control. Anisometric synthesis is attained by using an expanded sample structure called the warping image stack, together with a quadrant searching step and a continuity matching approach. Appearance control is achieved by associating each partition of the texture to a certain guiding vector, which arranges the partition to have corresponding local rotation and scaling. The experiments show that our method can produce textures with natural and flexible effect.